2004
DOI: 10.1016/j.physletb.2004.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Perturbative odderon in the dipole model

Abstract: We show that, in the framework of Mueller's dipole model, the perturbative QCD odderon is described by the dipole model equivalent of the BFKL equation with a Codd initial condition. The eigenfunctions and eigenvalues of the odderon solution are the same as for the dipole BFKL equation and are given by the functions E n,ν and χ(n, ν) correspondingly, where the C-odd initial condition allows only for odd values of n. The leading high-energy odderon intercept is given by α odd − 1 = 2 αs Nc π χ(n = 1, ν = 0) = 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
161
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(176 citation statements)
references
References 55 publications
13
161
1
1
Order By: Relevance
“…For this special odderon solution, the pomeron→two-odderon vertex becomes similar to the triple pomeron vertex. It is this special odderon solution which appears in the generalizations of the BK-equation [15,16]. Our more general version (3.10), on the other hand, allows to inlcude also other three-gluon solutions, such as the one found in [20,21] with intercept slightly below one.…”
Section: Jhep06(2018)095mentioning
confidence: 84%
See 3 more Smart Citations
“…For this special odderon solution, the pomeron→two-odderon vertex becomes similar to the triple pomeron vertex. It is this special odderon solution which appears in the generalizations of the BK-equation [15,16]. Our more general version (3.10), on the other hand, allows to inlcude also other three-gluon solutions, such as the one found in [20,21] with intercept slightly below one.…”
Section: Jhep06(2018)095mentioning
confidence: 84%
“…Since the structure of this odderon is practically identical to the pomeron, it became possible to radically simplify vertices for both pomeron →two odderon and odderon → odderon+pomeron transitions, which actually reduce to the triple pomeron form. This allowed to easily derive the coupled system of evolution of the pomeron and odderon including both transitions [15,16]. This system was analyzed in [26] where the angular dependence introduced by the pomeron→two odderon transition (POO) was drastically simplified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This corresponds to investigating multi-particle production in the kinematic region where the produced particles have transverse momenta higher than the saturation scale in the problem. It has been shown that in this limit the evolution equation for the dipole is the well-known BFKL equation [14], whereas the evolution equation for the odderon and quadrupole reduces to the BJKP equation for the energy dependence of a state of 3 or 4 Reggeized gluons [15][16][17] (see also [18] for a nice discussion of gluon Reggeization). It should be noted that this problem has also been investigated using a dual approach known as the KLWMIJ equation [19].…”
Section: Introductionmentioning
confidence: 99%